2013
DOI: 10.1017/thg.2013.60
|View full text |Cite
|
Sign up to set email alerts
|

Depression, Neuroticism, and Urinary Incontinence in Premenopausal Women: A Nationwide Twin Study

Abstract: Previous studies have found that major depression and neuroticism are positively associated with urinary incontinence (UI). However, the genetic contribution to these associations has never been investigated. In 2005, a total of 14,094 female twins born 1959-1985 in the Swedish Twin Registry participated in a comprehensive survey on common exposures and complex diseases. Structured questions provided information on UI, depressive symptoms, major depression, and neuroticism. A logistic regression model based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…We also know that in adults there is an association between anxiety and a higher incidence of urgency and frequency. 8,9 In the past there have been mixed results between the relationship of anxiety (neurotiscism) and intelligence, 10-12 but more recent work has found that it is necessary to remove the anxiety caused by the test to measure this appropriately. 13 Penney et al has found that there is a positive correlation between IQ and anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…We also know that in adults there is an association between anxiety and a higher incidence of urgency and frequency. 8,9 In the past there have been mixed results between the relationship of anxiety (neurotiscism) and intelligence, 10-12 but more recent work has found that it is necessary to remove the anxiety caused by the test to measure this appropriately. 13 Penney et al has found that there is a positive correlation between IQ and anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Enuresis is understood as a genetically determined developmental disorder, which is modulated by environmental factors; daytime wetting is also multifactorial with a complex interaction of genetic and environmental factors [10,[30][31][32]. There is evidence for genetic overlap of enuresis with ADHD [33] and affective disorders [34]. However, it is unclear whether this is due to the same set of risks manifesting as different disorders in different people, at different ages, or because ADHD/affective disorders causes enuresis (or both).…”
Section: Possible Mechanisms Explaining the Findingsmentioning
confidence: 99%
“…Enuresis is understood as a genetically determined developmental disorder, which is modulated by environmental factors; daytime wetting is also multifactorial with a complex interaction of genetic and environmental factors [9,[29][30][31]. There is evidence for genetic overlap of enuresis with ADHD [32] and affective disorders [33]. However, it is unclear whether this is due to the same set of risks manifesting as different disorders in different people, at different ages, or because ADHD/affective disorders causes enuresis (or both).…”
Section: Possible Mechanisms Explaining the Findingsmentioning
confidence: 99%